Advances in stem cell proteomics - Abazova, Nadeshda; Krijgsveld, Jeroen (Current opinion in genetics & development, 2017)
Stem cells are at the basis of organismal development, characterized by their potential to differentiate towards specific lineages upon receiving proper signals. To understand the molecular principles underlying gain and loss of pluripotency, proteomics plays an increasingly important role owing to technical developments in mass spectrometry and implementation of innovative biochemical approaches. Here we review how quantitative proteomics has been used to investigate protein expression, localization, interaction and modification in stem cells both in vitro and in vivo, thereby complementing other omics approaches to study fundamental properties of stem cell plasticity.